2017
DOI: 10.1128/aac.01166-17
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Posaconazole Tablets and Monte Carlo Simulations To Determine whether All Patients Should Receive the Same Dose

Abstract: Posaconazole is extensively used for prophylaxis for invasive fungal infections. The gastro-resistant tablet formulation has allowed the bioavailability issues encountered with the oral suspension to be overcome. However, overexposure is now frequent. This study aimed to (i) describe the pharmacokinetics of posaconazole tablets in a real-life cohort of patients with hematological malignancies and (ii) perform Monte Carlo simulations to assess the possibility that the daily dose can be reduced while keeping a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 21 publications
5
49
1
Order By: Relevance
“…2). This was consistent with previous adult models [15,19,20]. Our estimated CL/ F and apparent volume related to the tablet formulation and standardised to a 70-kg individual were 14.95 L/h and b dose estimated dose in mg/m 2 for suspension bioavailability to drop to half that of the tablet, CI confidence interval, CL/F apparent clearance, CV coefficient of variation, Ka absorption rate constant, h D fractional decrease in suspension bioavailability with patients with diarrhea, h P fractional decrease in suspension bioavailability with patients taking proton pump inhibitors, RSE relative standard error, V/F apparent volume 201.68 L, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…2). This was consistent with previous adult models [15,19,20]. Our estimated CL/ F and apparent volume related to the tablet formulation and standardised to a 70-kg individual were 14.95 L/h and b dose estimated dose in mg/m 2 for suspension bioavailability to drop to half that of the tablet, CI confidence interval, CL/F apparent clearance, CV coefficient of variation, Ka absorption rate constant, h D fractional decrease in suspension bioavailability with patients with diarrhea, h P fractional decrease in suspension bioavailability with patients taking proton pump inhibitors, RSE relative standard error, V/F apparent volume 201.68 L, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Our estimated CL/ F and apparent volume related to the tablet formulation and standardised to a 70-kg individual were 14.95 L/h and b dose estimated dose in mg/m 2 for suspension bioavailability to drop to half that of the tablet, CI confidence interval, CL/F apparent clearance, CV coefficient of variation, Ka absorption rate constant, h D fractional decrease in suspension bioavailability with patients with diarrhea, h P fractional decrease in suspension bioavailability with patients taking proton pump inhibitors, RSE relative standard error, V/F apparent volume 201.68 L, respectively. In a recent study of adults, CL/F and apparent volume were estimated to be 7.3 L/h and 420 L, respectively [19], which fall within the 95% confidence intervals of our estimates (Table 2). Fixing the absorption rate to that previously reported in adults had a negligible effect on model fit, and the flat profiles, the fact our data did not include any patients sampled after their first dose, and the limited number of samples in the absorption phase all account for this.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…and Mucorales that had high MICs in our patient. This finding is consistent with a previous population pharmacokinetic study that found that approximately 72.6% of patients achieved the posaconazole minimum concentration target after 48 hrs of treatment 20. This may be due to the inter-individual variability and inter-occasion variability pharmacokinetic characteristics of posaconazole 20.…”
Section: Discussionsupporting
confidence: 92%
“…This greater POS C min could theoretically result in a greater risk of side effects, although no study has yet clearly highlighted increased toxicity with the POS tablet formulation [2,[9][10][11][12][13][14]. Hence, no upper threshold for the POS C min has yet been proposed, even if some authors have suggested that dose reduction could be feasible for at least half of patients [15,16]. It is therefore necessary to precise the upper limit of POS C min above which POS dosing could be reduced.…”
Section: Introductionmentioning
confidence: 99%